Sensory and motor deficits exist on the non-injured side of patients with unilateral tendon pain and disability—implications for central nervous system involvement: a systematic review with meta-analysis. Issue 19 (21st October 2013) - Heales, L J; Lim, E C W; Hodges, P W; Vicenzino, B
Abstract : Introduction: Tendinopathy manifests as activity-related tendon pain with associated motor and sensory impairments. Tendon tissue changes in animals present in injured as well as contralateral non-injured tendon. This review investigated evidence for bilateral sensory and motor system involvement in unilateral tendinopathy in humans. Methods: A comprehensive search of electronic databases, and reference lists using keywords relating to bilateral outcomes in unilateral tendinopathy was undertaken. Study quality was rated with the Epidemiological Appraisal Instrument and meta-analyses carried out where appropriate. Analysis focused on comparison of measures in the non-symptomatic side of patients against pain-free controls. Results: The search revealed 5791 studies, of which 20 were included (117 detailed reviews, 25 met criteria). There were 17 studies of lateral epicondylalgia (LE) and one each for patellar, Achilles and rotator cuff tendinopathy. Studies of LE were available for meta-analysis revealing the following weighted pooled mean deficits: pressure pain thresholds (−144.3 kPa; 95% CI −169.2 to −119.2 p<0.001), heat pain thresholds (−1.2°C; 95% CI −2.1 to −0.2, p<0.001), cold pain thresholds (3.1°C; 95% CI 1.8 to 4.4, p<0.001) and reaction time (37.8 ms; 95% CI 24.8 to 50.7, p<0.001). Discussion: Deficits in sensory and motor systems present bilaterally in unilateral tendinopathy. This implies potential central nervous system involvement. This indicates that rehabilitation should consider the contralateral side of patients. Research of unilateral tendinopathy needs to consider comparison against pain-free controls in addition to the contralateral side to gain a complete understanding of sensory and motor features.